2015
DOI: 10.46743/2160-3715/2012.1695
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory of Inductive Qualitative Research Education: Results of a Meta-Data-Analysis

Abstract: This paper reports on the first stage of a meta-study conducted by the authors on primary research published during the last thirty years that focused on discovering the experiences of students learning qualitative research. The authors carried out a meta-analysis of the findings of students’ experiences learning qualitative research included in twenty-five published articles. Using constructivist grounded theory to analyze the experience of those seeking to learn qualitative research, including factors that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…Seven themes were identified including experiential learning, practice-based materials and workshops, course structure, peer or collaborative work, apprenticeship model, competence of qualitative research trainers, and teaching resources. Although this review considered research on teaching qualitative research, five of the seven identified themes focused on student learning-notably reinforcing the significance of experiential learning (Cooper et al, 2012).…”
Section: Teaching Qualitative Research Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Seven themes were identified including experiential learning, practice-based materials and workshops, course structure, peer or collaborative work, apprenticeship model, competence of qualitative research trainers, and teaching resources. Although this review considered research on teaching qualitative research, five of the seven identified themes focused on student learning-notably reinforcing the significance of experiential learning (Cooper et al, 2012).…”
Section: Teaching Qualitative Research Onlinementioning
confidence: 99%
“…Using the TPACK framework, which defines teacher knowledge in terms of technological, pedagogical, and content knowledge, Snelson analyzed 11 articles; her findings indicated that "…online qualitative research methods educators choose course goals, instructional modules, and topics in a manner consistent with instructional design approaches" (p. 2799). Noticeably absent from Snelson's review was attention to experiential learning for online students, which was emphasized in the other reviews (Cooper et al, 2012;Wagner et al, 2019). However, Snelson's research called for greater attention to experiential learning in future studies of teaching qualitative research online.…”
Section: Teaching Qualitative Research Onlinementioning
confidence: 99%
“…However, at times, in my experience as a trainer in counselling and psychotherapy, research students can rather feel as if they are getting stuck going round in circles as they learn to make sense of the complexities of the research process. Fortunately, research assures me that this is not solely down to my particular teaching style but is a common experience; research students are impacted not just cognitively but emotionally and experientially by engaging with research (e.g., Cooper, Chenail & Fleming, 2012). Research can be daunting for newcomers as my own article in this issue highlights, and it is rarely the topic in the curricula that students look forward to the most.…”
Section: Dr Janet E Pennymentioning
confidence: 99%
“…Importantly, this included not only texts in political science and IR but also a way into teaching qualitative methods, a topic which often presents many challenges for both students and those who teach them. Studies suggest that students tend to grasp research methods better when faced with active, experiential learning opportunities (Cooper, Chenail & Fleming, 2012). Autoethnography allows for this and in the process helps illustrate the absurdity of papers where the researchers themselves are often grammatically absent from methods sections, implying that their persona had no effect on results (Billig, 2013).…”
Section: Autoethnography As Pedagogymentioning
confidence: 99%